Capsid containing virus like particle vaccine against Zika virus made from a stable cell line. Issue 48 (15th November 2019) - Garg, Himanshu; Mehmetoglu-Gurbuz, Tugba; Ruddy, Gregory M.; Joshi, Anjali
Highlights: There remains a need for a safe and effective Zika virus (ZIKV) vaccine. We developed stable cell lines secreting ZIKV CprME Virus Like Particles (VLPs). The CprME VLPs generate a superior neutralizing antibody response. Immunization with CprME VLPs protected mice against ZIKV challenge. Abstract: Zika virus infection during pregnancy is associated with severe birth defects including microcephaly in the new born. The lack of specific treatment calls for the development of a safe and effective vaccine for use in pregnant women. We recently tested the efficacy of a Virus Like Particle (VLP) vaccine for Zika virus in mice and found that Capsid-preMembrane-Env (CprME) VLPs generated a better neutralizing antibody response than preMembrane-Env (prME) VLPs. The superiority of CprME VLPs suggested that inclusion of capsid in the vaccine may enhance the immune response. However, production of CprME VLPs requires co-expression of NS2B-3 protease, which creates a major hurdle for generation of stable cell lines. To overcome this limitation, we generated a bicistronic vector that expresses CprME and NS2B-3 using an IRES sequence. This bicistronic expression cassette, in a lentiviral vector, was used to create a stable cell line that constitutively secretes CprME VLPs. The expression of NS2B-3, presence of capsid in the secreted VLPs, efficiency of VLP release, and stability of the cell line was extensively tested. Antigen sparing studies in mice using prME and CprME VLPs, both derived from stable cell lines, confirmed the superiority of CprME VLPs in generation of neutralizing antibody response. Capsid specific antibodies were detected in CprME VLP immunized mice providing mechanistic insights into the superiority of these VLPs. Challenge of CprME VLP immunized mice with Zika PRVABC59 showed complete protection against day 3 viremia further validating the efficacy of the vaccine. Our study is the first to generate a stable cell line secreting Zika CprME VLPs via natural NS2B-3 cleavage, demonstrate incorporation of capsid in CprME VLPs and complete protection in challenge studies. This is a major advancement for the Zika vaccine platform that is safe for use in pregnant women and readily scalable for use in developing countries.